أحباس جربة: أزمة مؤسسة أم تحول مجتمع محلي - الباهي, مبروك (Les Iles Méditerranéennes: relais de civilisations : actes de colloque international collectif, 2004)
Keywords: Famille Bin Ayyad; Hadharbash, mosquée (Midoun, Djerba); Jadariyya, mosquée al- (Jaabira, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Waqf (fondations) -- Djerba

جزيرة جربة تحت حكم عائلة السمومني (688-967ه/1289-1560م) - الزرويل, صالح (مجلة هيرودوت للعلوم الإنسانية والاجتماعية, 2023)
Keywords: Famille Bin Ayyad; Famille Bin Jlūd; Famille Samūmnī; Ghuraba, mosquée al- (Houmt Souk, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Vie politique -- Djerba; يحيى بن زكرياء السمومني (أبو زكرياء) (حيٌّ في: 916هـ/ 1510م)

Modern Ibadi Books on the Move: the “al-Shaykh Mosque” Library in Houmt Souk (Djerba, Tunisia) | رحلات الكتب الإباضية الحديثة: مكتبة “جامع الشيخ” بحومة السوق (جربة، تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2025)
This summer, I have had the chance to return to Djerba (Tunisia) and work with my colleague from Ibadica, Si Mahfoudh Dahman, on documenting part of another library collection there. This month has…
Keywords: Manuscrits -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba)

Résistance et dévotion: Anciens sanctuaires ibadites de Djerba - Prevost, Virginie (British Institute for Libyan and Northern African Studies, 2023)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Malāq, mosquée (Oued Zbib, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Yunus b. Taarit, mosquée (Fatou, Djerba)

مدونة مساجد جربة - المرابط, رياض (المعهد الوطني للتراث, 2002)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Mīmūn, mosquée (Beni Bandou, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Ghazi Mustafa, Burj (Houmt-Souk, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jadīd (Būmallāl), mosquée al- (Boumellal, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Marākshī, mosquée al- (Houmt-Souk, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Qṣārīn, mosquée (Houmt Souk, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Beni Bandou, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Bu Sa'id, mosquée (Boumellal, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Ibrahim al-Jumni, mosquée (Houmt Souk, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Sīdī Bin ʿIsā, zaouia (Houmt-Souk, Djerba); Sīdī Būʿakāzīn, mosquée (Houmt-Souk, Djerba); Sīdī Msāhil, mosquée (Beni Bandou, Djerba); Sīdī Sālim, mosquée (Khanfous, Djerba); Sīdī Zītūnī, zaouia (Houmt Souk, Djerba); Sīdī al-Baḥrī, mosquée (Houmt-Souk, Djerba); Sīdī ʿAbd al-Qādir, zaouia (Houmt-Souk, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Turuk, mosquée al- (Houmt Souk, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Ḥashānī, mosquée al- (Ghizen, Djerba)